PENGARUH SANKSI PERPAJAKAN DAN KEADILAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DENGAN DIMEDIASI KUALITAS PELAYANAN: Studi Pada Wajib Pajak Usaha Mikro Kecil dan Menengah yang Terdaftar di KPP Kebayoran Lama - Alda Farida; Wiwit Irawati (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to analyze the Effect of Tax Sanctions and Tax Fairness on MSME Taxpayer Compliance Mediated by the Quality of Micro, Small and Medium Enterprises Services Registered at the KPP Kebayoran Lama. The population in this study are 2,569 MSME taxpayers registered at the Kebayoran Lama KPP in 2021. This type of research is associative research with primary and secondary data approaches. The sample collection technique for this study was non-probability sampling using SPSS version 26 software. The results of this study indicate that (1) Tax Sanctions do not affect Service Quality, (2) Tax Justice affects Service Quality, (3) Tax Sanctions affect Compliance Taxpayers, (4) Tax Justice affects Taxpayer Compliance, (5) Taxpayer Compliance affects Service Quality, (6) Service Quality does not mediate between Tax Sanctions and Taxpayer Compliance, (7) Service Quality does not mediate between Tax Fairness on Taxpayer Compliance